State Islamic Orthodoxies and Islamic Education in Malaysia and Indonesia - Azmil Tayeb, (Kajian Malaysia, 2017)
This paper compares state Islamic orthodoxy in Indonesia and Malaysia by using Islamic education curriculum for senior high schools as my case study. I argue that Malaysian Islamic Development Agency (Jabatan Kemajuan Islam Malaysia, JAKIM) in Malaysia has been more successful in exerting its orthodox values in the Islamic education curriculum than its counterpart Indonesian Council of Ulama (Majelis Ulama Indonesia, MUI) due to three factors: clear institutional objective; ideological cohesion among state institutions overseeing Islamic education; and patterns of Islamisation in the society that provide a conducive milieu for such orthodox ideals to thrive. In this paper I limit the scope of time and space to state Islamic orthodoxy in Indonesia and Malaysia from the late 1970s to present. I then choose three common topics found in Islamic education curriculum for senior high schools in Indonesia and Malaysia – pluralism/freedom of religion, marriage, and civic responsibility/governance – as examples of JAKIM's ideological dominance in Malaysia and the multifaceted nature found in Indonesian state Islamic orthodoxy.